Pengaruh Puding Daun Kelakai (Stenochlaena Palustris) Terhadap Peningkatan Kadar Hemoglobin Pada Remaja Putri Anemia di Desa Bungursari Tahun 2024 - Prihantini, Titin; Irawati, Ratna (Jurnal Sosial Teknologi, 2025)
Adolescent anemia is a health problem that requires attention. As many as 23% of the prevalence of anemia among adolescent girls in the age group of 13-18 years in Indonesia in 2022.Based on the monitoring of adolescents in Bungursari Village, it was found that there are still many who complain of 5L (Lethargic, Tired, Weak, Tired, Negligent) and the results of the Hemoglobin examination are below normal as much as 55%. The cause of anemia is the lack of hemoglobin levels in red blood cells. Efforts to reduce the incidence of anemia by increasing iron levels, one of which is the administration of kelakai leaf pudding (Stenochlaena Palustris) which contains iron in 100 grams of leaves of 291.32 mg. To find out the effect of kelakai leaf pudding (stenochlaena palustris) on increasing hemoglobin levels of anemic adolescent girls in Bungursari Village in 2024. This study is a type of pre-experimental research with a two-group pretest and posttest design in the control group with 17 people educated and an intervention group with the administration of 17 kelakai leaf pudding (Stenochloena Palustris). The number of samples in this study was 34 people with inclusion and exclusion criteria with direct examination and observation techniques for 7 days. The results of this study showed that the average hemoglobin before action in the control group was 11.30 gr% to 11.94 gr%, and in the intervention group the average hemoglobin before and after being given kelai leaf pudding (stenochlaena palustris) from 11.25 gr% to 12.80 gr%. The statistical test uses a non-parametric statistical test, namely the Mann Withney test with a p-value of 0.000 (p-value < 0.05), meaning that there is an effect of increasing hemoglobin levels before and after being given kelakai leaf pudding (stenochlaena palustris). There is an effect of increasing hemoglobin levels with the administration of kelakai leaf pudding (stenochalaena palustris) in anemic adolescent girls. It is hoped that the administration of kelakai leaf pudding (stenochlaena palustris) as a non-pharmacological drug that can help prevent anemia.